(4x2-25)2-9(2x-5)2
phân tích đa thức thành nhân tử
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=x\left(x^2+2x+1-y^2\right)=x\left[\left(x+1\right)^2-y^2\right]=x\left(x+y+1\right)\left(x-y+1\right)\)
b) 4x2 - 25 + (2x + 5)2
= (2x + 5)(2x - 5) + (2x + 5)2
= (2x + 5)(2x - 5 + 2x + 5)
= 4x(2x + 5)
phân tích đa thức thành nhân tử
a, 4x2-25-(2x-5) (2x+7)
b, x3 +27 +(x +3) (x-9)
c, 4x2y2 -(x2 + y2- z2)
\(a,4x^2-25-\left(2x-5\right)\left(2x+7\right)\)
\(=\left(2x-5\right)\left(2x+5\right)-\left(2x-5\right)\left(2x+7\right)\)
\(=\left(2x-5\right)\left(2x+5-2x-7\right)\)
\(=-2\left(2x-5\right)\)
\(b,x^3+27+\left(x+3\right)\left(x-9\right)\)
\(=\left(x+3\right)\left(x^2-3x+9\right)+\left(x+3\right)\left(x-9\right)\)
\(=\left(x+3\right)\left(x^2-3x+9+x-9\right)\)
\(=\left(x+3\right)\left(x^2-2x\right)\)
\(=x\left(x+3\right)\left(x-2\right)\)
=.= hok tốt!!
b) 4x2 – 9 + (2x + 3)2
= (4x2 - 9) + (2x + 3)2
= (2x + 3)(2x - 3) + (2x + 3)2
= (2x + 3)(2x - 3 + 2x + 3)
= 4x(2x + 3)
\(=\left(4x-x-1\right)\left(4x+x+1\right)=\left(3x-1\right)\left(5x+1\right)\)
\(=\left(4x-x-1\right)\left(4x+x+1\right)=\left(3x-1\right)\left(5x+1\right)\)
\(x-3\sqrt{x}+2=x-\sqrt{x}-2\sqrt{x}+2=\sqrt{x}\left(\sqrt{x}-1\right)-2\left(\sqrt{x}-1\right)=\left(\sqrt{x}-2\right)\left(\sqrt{x}-1\right)\)
\(x-3\sqrt{x}+2=\left(\sqrt{x}-1\right)\left(\sqrt{x}-2\right)\)
1) \(x\left(4x+1\right)\)
2) \(3\left(x-3y\right)\)
3) \(\left(2x+1\right)\left(2x+1+2\right)=\left(2x+1\right)\left(2x+3\right)\)
a: \(4x^2-x-5=\left(4x-5\right)\left(x+1\right)\)
b: \(x^2-2x-15=\left(x-5\right)\left(x+3\right)\)
a) \(x^2-9+2\left(x+3\right)=\left(x-3\right)\left(x+3\right)+2\left(x+3\right)=\left(x+3\right)\left(x-3+2\right)=\left(x+3\right)\left(x-1\right)\)
b) \(x^2-10x+25-3\left(x-5\right)=\left(x-5\right)^2-3\left(x-5\right)=\left(x-5\right)\left(x-5-3\right)=\left(x-5\right)\left(x-8\right)\)
c) \(x^3-4x^2+3x=x\left(x^2-4x+3\right)=x\left(x-1\right)\left(x-3\right)\)
\(\left(4x^2-25\right)^2-9\left(2x-5\right)^2=\left(4x^2-25\right)^2-\left(6x-15\right)^2\)
\(=\left(4x^2-25-6x+15\right)\left(4x^2-25+6x-15\right)\)
\(=\left(4x^2-6x-5\right)\left(4x^2+6x-40\right)=2\left(x+4\right)\left(2x-5\right)\left(4x^2-6x-5\right)\)